2005
DOI: 10.1145/1048687.1048690
|View full text |Cite
|
Sign up to set email alerts
|

Throwing versus walking as indicators of distance perception in similar real and virtual environments

Abstract: For humans to effectively interact with their environment, it is important for the visual system to determine the absolute size and distance of objects. Previous experiments performed in full-cue, real-world environments have demonstrated that blind walking to targets serves as an accurate indication of distance perception, up to about 25 m. In contrast, the same task performed in virtual environments (VEs) using head-mounted displays shows significant underestimation in walking. To date, blind walking is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
89
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 18 publications
12
89
0
8
Order By: Relevance
“…These experiments have consistently demonstrated that VE users judge the distances to targets as shorter than they are intended to be. Underestimation of distance has been demonstrated through verbal reports of distance (Mohler et al, 2006), blind walking to previously viewed targets (Durgin et al, 2002;Loomis & Knapp, 2003;Richardson & Waller, 2007;Willemsen & Gooch, 2002;Witmer & Sadowski, 1998), and throwing measures (Sahm et al, 2005) and are unlikely in isolation to be the result of the limited field of view or the mechanics of HMDs (Willemsen, Colton, Creem-Regehr, & Thompson, 2009), stereo vision conflicts (Willemsen et al, 2008), or optical distortions inherent to HMDs (Kuhl, Thompson, & Creem-Regehr, 2008).…”
Section: Measures Of Distance Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments have consistently demonstrated that VE users judge the distances to targets as shorter than they are intended to be. Underestimation of distance has been demonstrated through verbal reports of distance (Mohler et al, 2006), blind walking to previously viewed targets (Durgin et al, 2002;Loomis & Knapp, 2003;Richardson & Waller, 2007;Willemsen & Gooch, 2002;Witmer & Sadowski, 1998), and throwing measures (Sahm et al, 2005) and are unlikely in isolation to be the result of the limited field of view or the mechanics of HMDs (Willemsen, Colton, Creem-Regehr, & Thompson, 2009), stereo vision conflicts (Willemsen et al, 2008), or optical distortions inherent to HMDs (Kuhl, Thompson, & Creem-Regehr, 2008).…”
Section: Measures Of Distance Perceptionmentioning
confidence: 99%
“…They walk, throw, and verbally respond as if distances are closer than they are intended to be (Durgin, Fox, Lewis, & Walley, 2002;Loomis & Knapp, 2003;Mohler, Creem-Regehr, & Thompson, 2006;Richardson & Waller, 2007;Sahm, Creem-Regehr, Thompson, & Willemsen, 2005;Thompson et al, 2004;Willemsen, Gooch, Thompson, & Creem-Regehr, 2008). Now, numerous research studies have explored many of the possible reasons for this systematic effect on distance judgments.…”
mentioning
confidence: 99%
“…We use both verbal reports and blind walking for the real world, however for the VE condition we use verbal reports as a response measure, since blind walking is in this case not possible. Although blind walking has less variability [Sahm et al 2005], it has been shown that some factors (quality of computer graphics) have no impact on responses involving locomotion, but they do influence verbal reports of egocentric distances [Kunz et al 2009]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent research by our group (Campos et al 2009) has obtained the same result with pointing during blind walking. Importantly, when egocentric distance cues are reduced, visually directed action indicates the same systematic errors in perceived distance that other measures of perceived distance indicate (Hutchison and Loomis 2006;Loomis et al 1998;Sahm et al 2005;Wu et al 2004).…”
Section: Introductionmentioning
confidence: 88%